Beyond Biblical theology : sacralized culturalism in Heikki Räisänen's hermeneutics - Eskola, Timo. (Biblical Interpretation Series, 2013)
Reading Heikki Räisänen's hermeneutics in context, Timo Eskola explores the development of Western New Testament interpretation. Reclaiming a Wredean approach to the Scriptures, Räisänen focuses on tradition and interpretation. He builds on Weberian sociology, adopted through Peter Berger's theories, and substitutes sacralized culturalism for biblical theology. After examining fourteenth century Quran-criticism and its impact on Reimarus, Eskola discusses the genesis of the revised history-of-religion theory that Räisänen developed when investigating the Quran's relationship to the Bible. Sociology then becomes a link between standard historicism and poststructuralism as Räisänen reinterprets Berger's sociology of knowledge. Räisänen's sacralized culturalism finally becomes the theory from which his magnum opus The Rise of Christian Beliefs has been written.